2009
DOI: 10.2528/pier09101204
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Scattering by Large Inhomogeneous Bi-Anisotropic Objects Using Aim

Abstract: Abstract-In this paper, electromagnetic scattering of a plane wave by large inhomogeneous arbitrarily shaped bi-anisotropic objects is solved by Adaptive Integral Method (AIM). Based on Maxwell equations and constitutive relationship for general bi-anisotropic media and using Volume Integral Equations (VIE), the electromagnetic fields are derived as functions of equivalent volume sources. Then the integral equations are discretized using Method of Moments (MoM). Because of the dense matrix property, MoM cannot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Such heavy computation complexity and memory cost are undesirable in many applications, e.g. the reconstruction of largescale induced electric or current density in discontinuous media in computational electromagnetics [19][20][21][22][23][24] or in radar signal research domain [25,26]. Therefore, it is necessary to reduce the computation time and the memory complexity in the G-IPRM.…”
Section: Introductionmentioning
confidence: 99%
“…Such heavy computation complexity and memory cost are undesirable in many applications, e.g. the reconstruction of largescale induced electric or current density in discontinuous media in computational electromagnetics [19][20][21][22][23][24] or in radar signal research domain [25,26]. Therefore, it is necessary to reduce the computation time and the memory complexity in the G-IPRM.…”
Section: Introductionmentioning
confidence: 99%
“…It usually requires O(N 2 ) memory to store the impedance matrix and O(N 2 ) operations to perform the matrix-vector product via an iterative solver, where N is the number of unknowns. The memory requirements and CPU time for solving the matrix equation are dramatically reduced by using some fast algorithms in the MoM such as Precorrected-FFT method (P-FFT) [7,8], Adaptive Integral Method (AIM) [9][10][11][12][13][14] and Multilevel Fast Multipole Algoithm (MLFMA) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate the analysis of electrically large antennas, the AIM has been used to reduce the memory requirements and accelerate the matrix-vector multiplications in the iterative solver. Different from the existing AIM codes [9][10][11][12][13][14], the Gauss interpolation scheme is used in our implementation of AIM. Numerical results for a cube mounted on a monopole and two monopoles placed on a helicopter are presented in Section 4.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiments reported in [5][6][7], we showed that updating a preconditioner with eigenvectors associated to a few small eigenvalues of the preconditioned matrix can lead to a significant reduction of the number of iterations of Krylov subspace methods in the solution of dense linear systems arising from the Method of Moments discretization of integral operators in electromagnetic scattering. Scattering analysis continues to receive much attention in electromagnetics research, see e.g., [15,25,30,31,37].…”
Section: Introductionmentioning
confidence: 99%